Measurement Quality of Life in People with Diabetes Mellitus using EQ-5D-5L, SF-6D, and QWB-SA - Nugraha, Akbar; Endarti, Dwi; Andayani, Tri Murti (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Quality of life is considered a humanistic outcome that can be used as a utility value in cost-utility analysis to compare therapeutic interventions. Diabetes mellitus can affect quality of life Objective: This study aimed to assess the utility values among patients diagnosed with diabetes mellitus and examine their correlation with patient characteristics. This study provides the first comparison of utility values derived from the EQ-5D-5L, SF-6D, and QWB-SA among Indonesian patients with diabetes mellitus in a primary care setting, offering locally relevant evidence for cost-utility analyses and highlighting the sociodemographic and clinical factors influencing QoL. Methods: Utility values were measured using the EuroQol Five-Dimension Five-Level (EQ-5D-5L), Short Form Six-Dimension (SF-6D), and Quality of Well-Being Self-Administered Scale (QWB-SA). The research design was cross-sectional, with a sample of Prolanis program members from community health centers in Gunung Kidul, Surakarta, Surabaya, and Madiun. Patient responses were converted to utility scores. Correlations between utility values and patient characteristics were analyzed using the Mann–Whitney or independent t-tests. Results: Utility scores obtained from EQ-5D-5L, SF-6D, and QWB-SA showed significant differences across instruments, with mean values of 0.89 ± 0.1575, 0.92 ± 0.0932, and 0.66 ± 0.1229, respectively. Conclusion: The utility scores of patients with diabetes mellitus measured using the EQ-5D-5L, SF-6D, and QWB-SA questionnaires showed significant differences. Patient characteristics that significantly influenced utility values included education level, employment status, income level, blood glucose control, and the presence of comorbidities.